Selected issues of tribological processes in road transport influence - Kulczycki, Andrzej; Kaźmierczak, Urszula; Kałużny, Jarosław; Dzięgielewski, Wojciech (Studia Ecologiae et Bioethicae, 2018)
This article investigates the issue of the environmental impact of car transport. This topic is discussed in the context of tribological processes, which result in increased fuel consumption and consequently increased emissions of exhaust gas components. Based on data found in the literature, the share of frictional resistance in the total fuel consumption of individual cars, trucks and buses was determined. Using statistical data for Poland, the effects of friction processes in individual vehicle groups on the annual CO2 emissions from transport vehicles were also determined. The final part of the paper presents the results of the preliminary research on the possibility of lowering the friction resistance in various friction nodes found in motor vehicles by introducing carbon nanomaterials into the lubricating oils.